Harnessing unprotected deactivated amines and arylglyoxals in the Ugi reaction for the synthesis of fused complex nitrogen heterocycles - Gómez-Ayuso, Javier; Pertejo, Pablo; Hermosilla, Tomás; Carreira-Barral, Israel; Quesada, Roberto; García-Valverde, María (Beilstein Journal of Organic Chemistry, 2024)
Piperazines and diazepines are examples of nitrogen heterocycles present in many marketed drugs highlighting their importance in the discovery of novel bioactive compounds. However, their synthesis often faces challenges, including complex functionalization and lengthy reaction sequences. Multicomponent reactions, notably the Ugi reaction, have emerged as powerful tools to address these hurdles. Here, we have demonstrated the possibility of using the combination of arylglyoxals and carboxylic acids tethered to nonprotected deactivated amines as a powerful strategy for the synthesis of complex fused heterocycles. The limited nucleophilic character of the amino group of the anthranilic acid, indole-2-carboxylic acid, pyrrole-2-carboxylic acid or N-phenylglycine has allowed the use of these compounds in the Ugi reaction without triggering competitive reactions. The additional functional group present in the resulting Ugi adduct can be leveraged in different post-condensation strategies to easily generate multiple fused nitrogen heterocycles including benzodiazepinone and piperazinone cores.
Keywords: arylglyoxals; deactivated amines; nitrogen heterocycles; Ugi reaction